Analisis Beban Kerja Fisik Petugas Lingkunagn Kampus XYZ Menggunakan Metode Cardiovascular Load (CVL) dan NASA-TLX - Rangga Faadihilah Ervan; Agnia Citra Sabrina; Jihan Zahra Nabiilah; Nissa Syifa Puspani (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
ABSTRACT Campus environmental staff play an important role in maintaining the cleanliness, comfort, and environmental quality of the university through activities such as sweeping campus areas, transporting waste, cleaning drainage systems, cleaning toilets, and maintaining gardens. These activities are carried out routinely with long working durations and require considerable physical effort. In addition to physical demands, campus environmental staff also experience mental pressure due to work targets, large work areas, and changing work environment conditions. However, physical and mental workload assessments on campus environmental staff are still rarely conducted in an integrated manner using both physiological and psychological methods, resulting in limited understanding of workers’ overall workload conditions. This study aims to analyze the physical and mental workload of campus environmental staff using the Cardiovascular Load (CVL) and NASA-TLX methods. The study involved 20 campus environmental staff at Widyatama University using a descriptive quantitative approach. Physical workload was measured through working pulse rate and resting pulse rate calculations using the CVL method, while mental workload was measured using the NASA-TLX questionnaire based on six assessment dimensions. The results showed that most respondents experienced high mental workload levels, with the dominant dimensions being Physical Demand and Effort. The CVL results indicated that all respondents were classified in the “improvement needed” category with CVL values ranging from 35.2% to 53.12%. Therefore, improvements in ergonomic work systems are needed to reduce work fatigue levels and improve worker productivity.Keywords: Physical Workload, Mental Workload, Campus Environmental Staff, CVL, NASA-TLX, Ergonomics. Keywords: Physical Workload, Mental Workload, CVL, NASA-TLX, Ergonomics.